Impacts and Prediction of Land Use/Cover Change on Runoff in the Jinghe River Basin, China - Ling Zhang; Weipeng Li; Zhongsheng Chen; Ruilin Hu; Zhaoqi Yin; Chanrong Qin; Xueqi Li (Land)
The Jinghe River flows through the gully area of the Loess Plateau, where soil erosion is relatively severe. With the intensification of human activities, quantitatively evaluating the impact of land use/cover change (LUCC) on runoff is of paramount importance. This study is based on the Soil and Water Assessment Tool (SWAT) and Patch-generating Land Use Simulation (PLUS) models, and quantitatively analyzes the effect of LUCC on runoff in the Jinghe River Basin (JRB) through land use data from 2000 to 2020 and predicted scenarios for 2030 that encourage development, farmland protection, and ecological protection. The results show that reductions in farmland, grassland, and forest areas promote runoff, while increases in construction land similarly contribute to greater runoff. In all 2030 scenarios, the JRB is dominated by farmland and grassland. The mean annual runoff of LUCC under the three simulated prediction scenarios shows an increasing trend compared to LUCC in 2020, and the distribution of mean annual runoff depth is roughly the same. In addition, there is a strong interconnection between land use types and runoff in their dynamic relationship. Within the LUCC scenario, the decrease in farmland and forest land, along with the growth of construction land area promote runoff, while grassland plays a suppressive role in runoff. The results can offer a scientific foundation for improving soil erosion as well as optimizing land use patterns in the JRB.